A field research on the effect of consumer sensitivity to equality in gender roles on their involvement in advertisements - Melis Gey; Cihan Becan (Connectist Istanbul University Journal of Communication Sciences)
In today’s world, brands try to strengthen their position in their industry and enhance their connexion with consumers by showcasing themselves on social issues to influence consumers and positively affect their brand image. Gender equality has recently become prominent among these social issues. Accordingly, this study examines consumers’ sensitivity to advertisements that promote gender equality. The aim of this study is to measure the impact of consumers’ sensitivity to equality in gender roles on their involvement in advertisements and to scrutinize their sensitivities and opinions regarding ads in this context. In the research, which employs a mixed-method approach, surveys were conducted online with 300 participants using convenience sampling, and in-depth interviews were conducted with 10 voluntary participants. To achieve the research objectives and test the hypotheses, one of the campaigns focussing on equality in household gender roles from the past year was selected after a pilot study and presented to the participants. According to the research findings, consumers’ sensitivity to equality in gender roles has a significant and positive impact on cognitive and affective involvement in advertisements. Furthermore, participants believed that the message conveyed in the ad could be beneficial in terms of gender equality sensitivity, but they also critically examined equality in household gender roles presented in the advertisement.